RHEOLOGICAL AND PHYSICAL-PROPERTIES OF POLYARYLATE/LCP BLEND SYSTEMS - HONG, SM; KIM, BC; HWANG, SS; KIM, KU (SOC PLASTICS ENG INC, 1993)
A polyarylate Unitika U-Polymer 100 (PAR) was melt blended with a thermotropic liquid crystalline polymer (LCP) Vectra A950, and the processing-morphology-properties relations were investigated. Inclusion of LCP slightly reduced T(g) of PAR. The PAR/LCP blend with the LCP content higher than 50 wt% exhibited a noticeable yield stress, particularly in the vicinity of crystal-to-nematic transition temperature (T(cn)). LCP lowered the blend viscosity above T(cn), and seemed to play a role as processing aid. The tensile strength of the blends was increased with increasing spin draw ratio and level of LCP, and the spinning temperature influenced tensile strength. The relaxation behavior under dynamic shear and resultant blend morphology based on WAXD and SEM analyses are discussed as well.
Keywords: LIQUID-CRYSTALLINE POLYESTER; LONG FLEXIBLE SPACER; THERMOTROPIC POLYESTER; MECHANICAL-PROPERTIES; POLYETHYLENE TEREPHTHALATE; POLYCARBONATE BLENDS; TRANS-ESTERIFICATION; CALCIUM-CARBONATE; FLOW PROPERTIES; POLYMER BLENDS